JUNIOR HIGH SCHOOL TEACHER CHALLENGES, PRACTICE AND STRATEGIES ON IMPLEMENTING DIFFERENTIATED INSTRUCTION IN EFL CLASSROOM: Received: 23rd July 2024, Revised: 21st May 2025, Accepted: 1st July 2025, Date of Publication: 11th November 2025 - Hengki Anggra Hermawan,; Fazri Nur Yusuf, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Indonesia through the Ministry of Education, Culture, Research and Technology has launched a new curriculum called Emancipated Curriculum as an answer to the learning loss that occurred during the Covid-19 pandemic. The Emancipated Curriculum demands that teachers should be responsive to student needs and student diversity by implementing Differentiated Instructions, but in its implementation, many teachers still face challenges in the implementations. This study aims to find out the teacher challenges, practices, and strategies in implementing differentiated Instruction in EFL Classroom in Pangandaran Regency, Indonesia. This study used a qualitative research method by using observation and interviews to collect data. A total of 10 EFL Junior High School teachers were observed and then interviewed to get more comprehends data. The results show that teachers still face challenges in implementing differentiated instruction, The first is due to lack of knowledge about differentiated instruction, the second is due to the lack of supporting infrastructure and inappropriate environment that didn’t support the implementation, and the third is due to the very large time allocation in preparing and implementing differentiated instruction. In its implementation, differentiated instruction has a huge impact in accommodating students' needs so that students can reach their maximum potential. In addition, the teaching and learning process becomes very meaningful because the learning process become students centred. Various strategies are carried out by teachers, including increasing their knowledge about differentiated instruction from various sources, various online and offline training, various good practices through learning communities, and maximizing local wisdom in differentiated learning.